Efisiensi energi, emisi karbondioksida, dan biaya bahan bakar beberapa jenis kompor masak di Kabupaten Manokwari Provinsi Papua Barat - Bernadetha Yohana Gebze; Ishak Semuel Erari; Elina Relawaty Situmorang (Cassowary, 2023)
Most Public Regency Manokwari West Papua Province had used kerosene as fuel to cook whereas kerosene was known very no friendly environment because of kerosene produced very high emission of carbon monoxide (CO2). For limit use kerosene fuel, need searching for stove using fuel that has high efficiency however CO2 emissions level and cost were low. Purpose from study this was identify a number of fficient stove in using fuel, CO2 emissions and cost of fuel were more low. Tested stoves were electrically induction stove with a number of power (300W, 700W, 1000W, 1200W, 1400W, 1600W, 1800W, 2000W), stove electricity element consisted of two powers (1100W and 500W), kerosene stove 22 wicks and 16 wicks and LPG stove . Method used in this study was semi-empirical method , where in this research use pure water as much as 500 ml, which is heated from 27 o C to 100 o C, with use stainless steel receptacle with cover from glass. Results of study showed that electrically induction stove with 2000W power given the fastest cooking time (2.15 minutes) however with 1400W power cooking time electrically induction stove more fast than the other stove. Highest efficiency obtained from electrically induction stove (84%-88%), elemen electric stoves 50%-53%, LPG stove 46.38%, and kerosene stove 10–12%. Emission of CO2, the most low obtained from electrically induction stove (182–190 g CO2), kerosene stove 130-153 g. Lowest cost for cooking 500 ml obtained from electrically induction stove with IDR. 94–106, elemen stove IDR. 150–180, LPG stove IDR 210, and kerosene stove IDR. 225–261. Electrically induction stove is the best stove, which had highest energy efficiency, CO2 emission level and cost were low.